Effect of Neonatal Exposure of Monosodium Glutamate in Kidney of Albino Mice – A Histological Study - Bhattacharya, Tapati; Ghosh, S.K. (Nepal Medical College Journal, 2019)
Monosodium Glutamate (MSG) is a commonly used food additive. Scientists have found that MSG has toxic effects in several tissues and organs like neurons, liver, testes, ovary, kidneys etc due to oxidative stress both after exposure in neonatal period as well as in adult animal models. Although various reports have suggested that MSG has damaging effect in kidneys only few histological studies are available. This study was done to observe any histological changes in kidneys of albino mice after neonatal exposure with MSG. Study showed significant changes in weight and volume of kidneys in gross morphology. Increased urinary space and dilatation of proximal convoluted tubules (PCT) and distal convoluted tubules (DCT) were constant finding in experimental animals. There were loss of luminal microvilli and reduced height of lining cells of both PCT and DCT.